Answer :

False

cos2 23° - sin2 67° =(cos 23°+sin 67°)(cos 23°-sin 67°)


((a2-b2) = (a+b)(a-b))


= [cos 23°+sin(90°-23°)] [cos 23°-sin(90°-23°)]


= (cos 23°+cos 23°)(cos 23°-cos 23°) (sin(90°-θ) = cos θ)


= (cos 23°+cos 23°).0


= 0, which is neither positive nor negative


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Merchant of Venice (Summary and Important Questions)Merchant of Venice (Summary and Important Questions)Merchant of Venice (Summary and Important Questions)30 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses